Mitigating Striga hermonthica parasitism and damage in maize using soybean rotation, nitrogen application, and Striga-resistant varieties in the Nigerian savannas - Kamara, A.; Menkir, A.; Chikoye, David; Tofa, A.I.; Fagge, A.A.; Dahiru, R.; Solomon, R.; Ademulegun, T.; Omoigui, L.; Aliyu, K.T.; Kamai, N. (Cambridge University Press, 2020)
Striga hermonthica infestation causes significant losses of maize yield in the Nigerian savannas and several technologies have been developed and promoted to control Striga in maize. However, since no single technology has been found to be effective against Striga, integrated management is needed to achieve satisfactory and sustainable Striga control. Both on-station and on-farm trials were undertaken from 2013 to 2015 in Bauchi and Kano States of Nigeria to evaluate the performance of integrated Striga control technologies. In the on-station trials, a soybean–maize rotation did not suppress Striga in maize in either location. However, nitrogen application suppressed and reduced Striga infection, except in Bauchi in 2014. The soybean–maize rotation accompanied by N application reduced Striga damage in both locations. On farmers’ fields, rotating soybean with maize significantly reduced Striga infection. At the same time, the use of maize varieties with a combined tolerance to drought and resistance to Striga parasitism also increased maize grain yield on farmers’ fields, probably due to three factors: a reduction in Striga infection, reduced effects of a mid-season moisture deficit, and increased uptake of nutrients from the soil. We concluded that the use of Striga-resistant maize varieties in combination with the application of N fertilizer and rotation with soybean could increase the productivity of maize in Striga-infested fields in the Nigerian savannas.